Training the next generation of operators: AFPM immersive learning. Issue 4 (19th February 2021) - Forest, Daniel D.
Abstract: Demographics of the petroleum refining and petrochemical industries have shown an aging workforce nearing retirement and being replaced by a younger generation of workers who learn and were taught differently. To address the challenge of building competency in the young workforce, the Immersive Learning Committee was created by the American Fuel & Petrochemical Manufacturers (AFPM), a trade association representing nearly all U.S. refining and petrochemical manufacturing capacity. AFPM members produce the fuels that drive the U.S. economy and the chemical building blocks integral to millions of products that make modern life possible. This paper will show how the work of both AFPM and its members is helping bridge the knowledge gap between generations of employees and addressing competency training challenges by developing a digital library of tools—including virtual reality and augmented reality simulations, as well as three‐dimensional assets, and other resources—for broad industry use. The work also assists member companies with their own development of training tools tailored to their unique facilities, processes or company practices. The pilot project, a fired heater training simulation using virtual reality, will be discussed in the paper, as well as a set of leading metrics currently being developed that will help industry understand the effectiveness of the tools.